Droplet thermometry based on an optimized two dye two-color laser-induced fluorescence concept - Ulrich, Hannah; Sigl, Sophie; Möhnle, Michael; Berrocal, Edouard; Zigan, Lars (Frontiers in Physics, 2023)
In this work two-color laser-induced fluorescence (2c-LIF) is applied to calibrate and measure the temperature in a micrometric monodisperse ethanol droplet chain. A dye mixture of fluorescein disodium (FL) and sulforhodamine 101 (SRh) is used, in order to form a sensitive signal ratio of one temperature dependent and one independent fluorophore. Spectral and planar fluorescence detection via a fiber-coupled spectrometer and a camera system, consisting of two sCMOS cameras, is setup around the droplet chain. Additionally, absorption measurements of the dye mixture in ethanol are conducted using a photo-spectrometer to analyze the temperature sensitivity of the dyes as well as potential re-absorption and fluorescence cross-talk effects. The spectral setup allowed an investigation of the wavelength range in which morphology dependent resonances (MDR) occur at the phase boundary of the droplet. Thus, the optical filters, determining the color channels in the camera system, are chosen to avoid detection of the lasing signal and providing maximal temperature sensitivity at the same time. The calibrated signal ratios are applied in temperature measurements of evaporating heated droplets in the droplet chain, showing the cooling with larger distance from the nozzle.